Improving the classification of upper limb disorders. (19th October 2011) - Harris, E Clare; Palmer, Keith; Linaker, Cathy; Cooper, Cyrus; Coggon, David
Abstract : Objectives: Experts disagree about the optimal classification of upper limb disorders (ULDs). To explore whether differences in associations with risk factors can offer a framework for choosing between case definitions in aetiological research and surveillance, we conducted a systematic review. Methods: Reports with estimates of relative risk (RR) for >1 case definition relative to identical occupational exposures were identified from (i) systematic reviews of ULD and occupation and (ii) by hand searching five peer-review journals published over the past two decades. We abstracted details of case and exposure definitions and paired estimates of RR, for alternative case definitions with identical occupational exposures. Differences in RR between paired definitions were expressed as the ratio of RRs, typically using that for the more elaborate of the two definitions as the numerator. Results: The 21 eligible reports yielded 320 pairs of RRs (82, 75 and 163 respectively at shoulder, elbow, and distal arm). Ratios of RRs were often <1 (46%), the median ratio overall and by anatomical site being close to unity. In only 2% of comparisons did ratios reach >4. Conclusion: More elaborate case definitions of ULD (eg, those involving physical signs, more specific symptom patterns, and additional investigations) yield similar associations with occupational risk factors to those using simpler definitions. Thus, for purposes of aetiological research and surveillance, simple case definitions will often suffice. Our findings also provide a justification for pooling data on risk factors in meta-analyses, despite differences in case definition.